Numerical investigation of CuO-water nanofluid turbulent convective heat transfer in square cross-section duct under constant heat flux. Issue 6 (1st August 2016) - Ting, Hsien-Hung; Hou, Shuhn-Shyurng
Abstract : Purpose: – The purpose of this paper is to numerically investigate the convective heat transfer of water-based CuO nanofluids flowing through a square cross-section duct under constant heat flux in the turbulent flow regime. Design/methodology/approach: – The numerical simulation is carried out at various Peclet numbers and particle concentrations (0.1, 0.2, 0.5, and 0.8 vol%). The finite volume formulation is used with the semi-implicit method for pressure-linked equations algorithm to solve the discretized equations derived from the partial nonlinear differential equations of the mathematical model. Findings: – The heat transfer coefficients and Nusselt numbers of CuO-water nanofluids increase with increases in the Peclet number as well as particle volume concentration. Also, enhancement of the heat transfer coefficient is much greater than that of the effective thermal conductivity at the same nanoparticle concentration. Research limitations/implications: – Simulation of nanofluids turbulent forced convection at very high Reynolds number is worth for further study. Practical implications: – The heat transfer rates through non-circular ducts are smaller than the circular tubes. Nevertheless, the pressure drop of the non-circular duct is less than that of the circular tube. This study clearly presents that the nanoparticles suspended in water enhance the convective heat transfer coefficient, despite low volume fraction between 0.1 and 0.8 percent. Adding nanoparticles to conventional fluids may enhance heat transfer performance through the non-circular ducts, leading to extensive practical applications in industries for the non-circular ducts. Originality/value: – Few papers have numerically studied convective heat transfer properties of nanofluids through non-circular ducts. The present numerical results show a good agreement with the published experimental data.